GENDER-BASED DIFFERENCES IN SELF-REGULATED LEARNING: A COMPARATIVE ANALYSIS OF THE SELF-REFLECTION PHASE AMONG UNIVERSITY STUDENTS - Haleema Sadia; Faiza Khurshid (Journal of Religion and Society, 2025)
This study investigates gender-based differences in self-regulated learning (SRL), with a specific focus on the self-reflection phase among university students. Self-reflection is a critical component of SRL, encompassing self-judgment and self-reaction, which enable learners to evaluate their performance and adjust strategies for future learning tasks. The purpose of this research is to compare how male and female students engage in self-judgment (evaluating their academic efforts and outcomes) and self-reaction (emotional and behavioral responses following performance assessments). Drawing on Zimmerman's theoretical model of SRL, this study employs a quantitative methodology using a validated Likert-scale questionnaire administered to a stratified sample of university students across different faculties in Khyber Pakhtunkhwa. Descriptive statistics and t-tests were used to analyze gender-based variations in self-reflective practices. The findings reveal significant differences in the self-reflection phase between male and female students. Female students exhibited stronger tendencies toward self-judgment, demonstrating a higher frequency of critical performance assessment and goal readjustment. In contrast, male students were more likely to express performance satisfaction and exhibit adaptive self-reactions. These findings highlight the importance of integrating gender-sensitive strategies in educational settings to enhance reflective learning. The study contributes to the growing body of literature on SRL by offering empirical evidence on how gender influences metacognitive and motivational dimensions of learning. It also underscores the need for academic interventions that nurture reflective skills in both male and female learners to promote academic success and lifelong learning competencies. Keywords: Gender-Based Differences, Self-Regulated Learning, Self-Reflection Phase, University Students